Associação entre função respiratória e sarcopenia em idosos comunitários - Ohara, Daniela Gonçalves (Universidade Federal de São Carlos, 2018)
The international scientific literature has shown the relationship between sarcopenia and respiratory function in the elderly, because of imparments both conditions cause, associated with the aging process. In the last decade, development of international studies that address sarcopenia and respiratory function has been increased, but in Brazil this this theme is still scarce and little explored. In order to elucidate these gaps in the literature about this thematic, this thesis originated two studies: The Study I, entitled "Association of pulmonary function and sarcopenia in community-dwelling elderly people in the Amazon region", presented an association of spirometric variables (pulmonary function) with sarcopenia and its indicators, as well as determining variable cut-off points to discriminate sarcopenia. The Study II, entitled "Respiratory muscle strength as a discriminator of sarcopenia in community-dwelling elderly: cross-sectional study", aimed to verify the association between respiratory muscle strength and sarcopenia and its indicators, as well as to determine cut-off points to discriminate sarcopenia. The results of Studies 1 and 2 demonstrated that associations of pulmonary function and respiratory muscle strength, such as forced vital capacity (FVC), forced expiratory volume in one second (FEV1), and forced expiratory flow in 25-75% (FEF25 -75%) of FVC (pulmonary function); maximal inspiratory pressure (MIP) and maximal expiratory pressure (MEP) (respiratory muscle strength), were associated with a sarcopenia and mostly, especially in the indicators of muscle strength and gait speed, even after adjustment, this being an inverse association, in other words, the increase in values obtained in spirometry and in manovacuometry decreases a probability of sarcopenia. Furthermore, it was possible to determine cut-off points for spirometric and respiratory muscle strength variables to predict sarcopenia. From this thesis, we concluded that the respiratory function was worse in sarcopenic elderly, and it was associated with the diagnosis of sarcopenia and its indicators. In addition, cut-off points of pulmonary function and respiratory muscle strength variables may be used as a tool to discriminate sarcopenia in community-dwelling elderly.
Association of respiratory function and sarcopenia in community-dwelling elderly people
Keywords: Sarcopenia; Espirometria; Testes de Função Respiratória; Força muscular; Idoso; Envelhecimento; Spirometry; Respiratory function tests; Muscle strength; Older adult; Aging; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL